Evaluation of the Antibacterial, Antioxidant and α-Glucosidase Inhibitory Activities of Withanolides from Physalis gracilis - Padierna, Gerardo; Pérez-Castorena, Ana L.; Martínez, Mahinda; Nieto-Camacho, Antonio; Morales-Jiménez, Jesús; Maldonado, Emma (Planta Medica International Open, 2018)
A chemical investigation of the leaves, flowers, and stems of Physalis gracilis led to the isolation of three withanolides identified as withanolide D (1), 24,25-dihydrowithanolide D (2), and withaphysacarpin (3). The structures of these compounds were determined by analyses of their spectroscopic data, including 1D and 2D NMR. The antibacterial, antioxidant, and α-glucosidase inhibitory activities of compounds 1 and 3 and derivatives 4 and 5 were evaluated. None of the compounds showed antioxidant or glucosidase inhibitory activity. Also, they were inactive against gram-negative bacteria. However, compound 3 was found active against Bacillus subtilis (MIC=65.5 µM) and compound 5 against Staphylococcus aureus (MIC=27.9 µM).
Keywords: Physalis gracilis; Solanaceae; withanolides; antibacterial activity; antioxidant activity; α-glucosidase inhibition